PENGARUH PRODUCT, PRICE, PROMOTION & PROCESS TERHADAP PROSES KEPUTUSAN PENGGUNAAN JASA IJO WORKSHOP DI JAKARTA - Andreas Variandy; Tony Sitinjak (Bajang Institute, 2023)
Ijo Workshop here as a vehicle exterior maintenance solution to keep vehicles well maintained amidst the hustle of daily activities. Through a variety of services and affordable prices, Ijo Workshop presence is expected to answer the needs that exist in society. This study try to understand which variable give the most influence into the decision of using Ijo Workshop’s services. This study involved variables such as product, price, promotion as in Kotler and Amstrong theory and also process as in Kotler and Keller theory as independent variables. Then, service usage decision process as the dependent variable. This study draws the hypothesis that each independent variable has a positive influence on the decision to use Ijo Workshop services. The results obtained show that all independent variables have a significant positive influence on the decision process for using Ijo Workshop services with process variable as the highest influence compared to other variables. The recommendation for subsequent research can also identify current variables with differen indicators and als other variables sucs as place, people and physical evidence, considering that based on testing, only 62.3% of the variables have been represented the effect. On the other hand, activities related to promotion need to be expanded where the promotion variable is least compare to another